DEVELOPMENT OF PERORAL HYPOLIPIDEMIC FORMULATION BASED ON SULFATED ARABINOGALACTAN IN THE FORM OF POTASSIUM SALT - Ya. A. Kostyro; K. V. Alekseev (Фармация и фармакология (Пятигорск))
An original heparinoid, sulfated arabinogalactan in the form of potassium salt, possessing anticoagulant and hypolipidemic activities, has been developed at  the A.E. Favorsky Irkutsk Institute of Chemistry Siberian Branch of the Russian Academy of Sciences.The aim was to develop solid peroral dose forms (capsules and film-coated tablets) for the prevention and treatment of atherosclerotic lesion of blood vessels on the basis of potassium salt of sulfated arabinogalactan which would be suitable for further clinical trials of these forms.Materials and methods. The following materials were used in the work: sulfated arabinogalactan in the form of potassium salt, obtained at the A.E. Favorsky Irkutsk Institute of Chemistry Siberian Branch of the Russian Academy of Sciences; Ludipress®; AEROSIL® 200 Pharma; calcium stearate; Aquacoat ECD. The powder mixtures were briquetted followed by tableting and application of the finished film coating Aquacoat ECD, and encapsulation in hard gelatin capsules.Results. Composition and technological characteristics of capsules and film-coated tablets were determined using physico-chemical and technological properties of sulfated arabinogalactan in the form of potassium salt. Technological parameters and quality indicators were determined for the solid pharmaceutical dose forms in accordance with the requirements of the State Pharmacopoeia of the Russian Federation of the XIVth edition. Conclusion. The optimum compositions and technology for the preparation of capsules and film-coated tablets based on potassium salt of sulfated arabinogalactan for the prevention and treatment of atherosclerotic lesion of blood vessels, were developed. The data obtained were used for the regulatory documentation design.